Stroke Risk, Practice and Health Promotion Guidance among Geriatric Patients: Randomized Control Trail - shoulkamy, Tasneem Ahmed-; Fouad, Rasha Ahmed; Abozeid, Hanan Abd- Allah (International Journal of Membrane Science and Technology, 2023)
Background: Stroke is one of the world’s chief reasons of death and infirmity among geriatric. Objective: The research at hand analyzed the association among the rFSRP and health promotion lifestyle and practice about stroke prevention among geriatric patients. Design: A randomized controlled experimental study was used in this study. This study included 85 study and 85 control participants. Methods: Participants were randomly selected and provided with an educational intervention on health-promoting lifestyle behaviors. Data were collected via Tool (I): demographic and clinical data of geriatric patients, Tool (II): Revised Framingham Stroke Risk Profile (R- FSRP) Tool (III): geriatric patients’ practices about stroke prevention, and Tool IV: Health Promoting Lifestyle Profile II (HPLP II) pre, and three months after the program intervention. Results: The data analysis revealed noteworthy dissimilarities between the experimental and control groups, which were deemed statistically significant and pre and follow - up intervention regarding (R- FSRP), practice and health promotion (p < 0.05.). Conclusion:The study concluded that the intervention program had a positive effect on stroke risk, practices and health promotion lifestyle.